Comment on "Optimizing Post‑Activation Performance Enhancement in Athletic Tasks: A Systematic Review with Meta‑analysis for Prescription Variables and Research Methods"...Xu K, Blazevich AJ, Boullosa D, et al. Optimizing Post-activation Performance Enhancement in Athletic Tasks: A Systematic Review with Meta-analysis for Prescription Variables and Research Methods. SPORTS MED. 2025;55(4):977-1008. - Mota, Gustavo R. (Sports Medicine, 2026)
This letter addresses methodological considerations in research on post-activation performance enhancement (PAPE), emphasizing the need to account for psychological factors such as participant expectations and placebo/nocebo effects. The author acknowledges the rigor of a recent PAPE review but suggests that future studies should include an active placebo condition alongside traditional control and experimental protocols to better isolate physiological effects from expectancy influences. Additionally, the letter recommends assessing participant expectations and maintaining strict assessor blinding to improve internal validity. These methodological enhancements aim to increase the reliability and reproducibility of PAPE research and clarify the true impact of conditioning activities on exercise performance.